How psychology majors can add value to your workforce - Ng, Alvin Lai Oon * (BusinessToday, 2022)
Psychology is the science of mind, brain, and behaviour, and it is very relevant in our lives. It uses science as a methodology and language to investigate cognitive, behavioural, and emotional functioning in relation to various factors such as biology, physiology, society, and the environment.